2015
DOI: 10.1080/00224499.2015.1065954
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ethnicity in Dating, Hanging Out, and Hooking Up: Sexual Scripts Among Hispanic and White Young Adults

Abstract: We examined the scripts associated with heterosexual Hispanic and White young adults' most recent initial sexual or romantic encounter using two samples of heterosexual undergraduates: 224 Hispanic students (49% female) and 316 White students (51% female). Scripts were identified for three types of encounters: dating, hanging out, and hooking up. The three scripts had more than half of their actions in common. Items such as get to know one another, feel aroused, and engage in physical contact were present acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 57 publications
2
63
3
4
Order By: Relevance
“…An inhabited approach to the study of women's sexual decision making as students adopts a new angle for understanding the variability of actor responses within similar organizational environments, and acknowledges the cultivation of unique campus cultures across the thousands of four-year universities in the United States. An inhabited approach to the study of campus sexual life also contributes to the broader literature on hookup cultures, which finds differences in sexual behavior and experience of hookups across individual identities (Ahrold and Meston 2010;Barrios and Lundquist 2012;Berntson et al 2014;Eaton et al 2015;Kuperberg and Padgett 2015;Owen et al 2010;Rupp et al 2014;Spell 2016), as well as in response to university structures, such as the size, racial and gendered composition of its undergraduate population, or the availability of on-campus housing (Adkins et al 2015;Allison and Risman 2014;Uecker 2015). The present study adds a different dimension to this literature in its finding that, in addition to negotiating sexual relationships in response to individual identities and structural constraints, women also frame their decisions to seek out or engage in particular sexual relationships in ways that are consistent with, or adaptive to, the broader organizational culture of a given school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inhabited approach to the study of women's sexual decision making as students adopts a new angle for understanding the variability of actor responses within similar organizational environments, and acknowledges the cultivation of unique campus cultures across the thousands of four-year universities in the United States. An inhabited approach to the study of campus sexual life also contributes to the broader literature on hookup cultures, which finds differences in sexual behavior and experience of hookups across individual identities (Ahrold and Meston 2010;Barrios and Lundquist 2012;Berntson et al 2014;Eaton et al 2015;Kuperberg and Padgett 2015;Owen et al 2010;Rupp et al 2014;Spell 2016), as well as in response to university structures, such as the size, racial and gendered composition of its undergraduate population, or the availability of on-campus housing (Adkins et al 2015;Allison and Risman 2014;Uecker 2015). The present study adds a different dimension to this literature in its finding that, in addition to negotiating sexual relationships in response to individual identities and structural constraints, women also frame their decisions to seek out or engage in particular sexual relationships in ways that are consistent with, or adaptive to, the broader organizational culture of a given school.…”
Section: Discussionmentioning
confidence: 99%
“…For those from lower socioeconomic backgrounds, financial constraints or preference for engagement in committed relationships render hookups undesirable or inaccessible (Allison and Risman 2014;Hamilton and Armstrong 2009). Studies of rates of hooking up by race find that students of color are less likely to report engagement in hookups than their white counterparts (Eaton et al 2015;Owen, Fincham, and Moore 2010), while others document a relationship between race and levels of acculturation for participation in casual sex (Ahrold and Meston 2010). While studies detail similar rates of participation in hookups among men and women (Kuperberg and Padgett 2015), women are less likely to engage in hookups involving sexual intercourse than men (Berntson et al 2014), are less likely to report satisfactory hookup experiences (Armstrong, England, and Fogarty 2012;Jozkowski and Satinsky 2013), and are more likely to be judged negatively for being "too" sexual (Allison and Risman 2013), than their male counterparts.…”
Section: Sex and Relationships On America's College Campusesmentioning
confidence: 99%
“…It has been shown that a number of sexual scripts exist and that casual sex can be highly scripted (e.g., Eaton, Rose, Interligi, Fernandez, & McHugh, 2016 ; Littleton, Tabernik, Canales, & Backstrom, 2009 ). Several researchers already hinted that television as a cultural storyteller partly aids in creating casual sexual scripts (e.g., Claxton & van Dulmen, 2013 ; Garcia, Reiber, Massey, & Merriwether, 2012 ; Heldman & Wade, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…This way of spending free time is interpreted by some researchers (Matthews et al, 2000;Tani, 2015) as 'hanging out', meaning 'to be around' or spending time somewhere with peers, usually for no particular reason and without doing anything noteworthy. Other researchers (Eaton, Rose, Interligi, Fernandez, & McHugh, 2015;Sleight, 2016;van Hessen, 1965) have pointed out that hanging out is also an opportunity for young people to meet dating partners. Researchers sometimes use different terms for this social phenomenon, for example, unstructured socializing (Hoeben, 2016;Hoeben & Weerman, 2016;Osgood et al, 1996), loitering (Akiyama, 2010) or sauntering (van Hessen, 1965).…”
Section: Introductionmentioning
confidence: 99%